2016
DOI: 10.1186/s12890-016-0263-8
|View full text |Cite
|
Sign up to set email alerts
|

Burden of asthma with elevated blood eosinophil levels

Abstract: BackgroundAsthma is a common chronic condition with an economic burden of almost $56 billion annually in the US. Biologic markers like blood eosinophils, that help predict the risk of exacerbation could help guide more optimal treatment plans and reduce cost. The purpose of this study was to determine whether healthcare resource use and expenditures vary by eosinophil level among patients with asthma.MethodsPatients with a diagnosis of asthma defined by ICD-9-CM code 493.xx between January 2004 and July 2011 w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
2
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(38 citation statements)
references
References 12 publications
1
34
2
1
Order By: Relevance
“…As early as 1975, Horn et al [15] observed that increased blood eosinophil counts correlate with increasing airway obstruction in patients undergoing a pulmonary function test. Since then, several observational studies have also revealed that increased blood eosinophils are associated with more severe airflow obstruction [16], more severe exacerbations [1720], lower odds of achieving asthma control [1719,21], and increased hospital costs [22,23]. Patients with eosinophilic inflammation generally respond well to inhaled corticosteroid.…”
Section: Introductionmentioning
confidence: 99%
“…As early as 1975, Horn et al [15] observed that increased blood eosinophil counts correlate with increasing airway obstruction in patients undergoing a pulmonary function test. Since then, several observational studies have also revealed that increased blood eosinophils are associated with more severe airflow obstruction [16], more severe exacerbations [1720], lower odds of achieving asthma control [1719,21], and increased hospital costs [22,23]. Patients with eosinophilic inflammation generally respond well to inhaled corticosteroid.…”
Section: Introductionmentioning
confidence: 99%
“…Disclosures: Authors have nothing to disclose. outcomes, after inhaled corticosteroid or targeting of airway eosinophilia by biologic agents 17,19 ; this makes the blood eosinophil count a feasible marker for monitoring severe asthma.…”
Section: Introductionmentioning
confidence: 99%
“…x10 9 /ml independently predicted exacerbation risk with an odds ratio of 1.31 (95%CI 1.07 to 1.6) (44). This remained an independent predictor for exacerbations, even in those with poor asthma symptom control (45), and showed the strongest association with the most severe exacerbations that result in hospital admission (odds ratio; 5.14, 95%CI, 1.76 to 14.99) (46). Combining elevated blood eosinophils together with exhaled nitric oxide may further define those at greatest risk of future asthma exacerbations (47).…”
Section: Poor Asthma Control and Type 2 Airway Inflammation In Acute mentioning
confidence: 91%